2020
DOI: 10.1590/s0102-865020200070000008
|View full text |Cite
|
Sign up to set email alerts
|

PPARG expression in colorectal cancer and its association with staging and clinical evolution

Abstract: Purpose To evaluate the gene expression of peroxisome proliferator activated receptors gamma (PPARG) in colorectal tumors and to correlate this data with clinical variables of the patients. Methods We analyzed the gene expression of PPARG in 50 samples of colorectal tumors using real-time reverse transcription polymerase chain reaction, and 20 adjacent normal tissue samples as control. The results of these quantifications were correlated with the respective patients’ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…To date, the involvement of PPAR-α as an oncogene has been recognised and PPAR-α has been found to be both overexpressed in CRC and correlated with poor prognosis [ 32 , 33 ]. On the contrary, several lines of research have shown that PPAR-γ plays a crucial role in regulating the growth of various cancers and its expression has been associated with a favourable prognosis for CRC [ 34 ]. Consistent with these data, we found that DMW was able to downregulate and upregulate the expression of PPAR-α and PPAR-γ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the involvement of PPAR-α as an oncogene has been recognised and PPAR-α has been found to be both overexpressed in CRC and correlated with poor prognosis [ 32 , 33 ]. On the contrary, several lines of research have shown that PPAR-γ plays a crucial role in regulating the growth of various cancers and its expression has been associated with a favourable prognosis for CRC [ 34 ]. Consistent with these data, we found that DMW was able to downregulate and upregulate the expression of PPAR-α and PPAR-γ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Yu-Chan Chang et al found the glucose transporter 4 promotes the oral cancer through the DDX58 signaling 22 . Andre Luiz Prezotto Villa et al found the expression of PPARG in colorectal cancer is related to the staging and clinical evolution 23 . Circadian gene clocks and its downstream molecules are related to many cell functions including metabolism, immune, proliferation, and differentiation [24][25][26][27][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Peiliang Geng et al found the genetic association of NFKBIA in cancer susceptibility 38 . Andre Luiz Prezotto Villa et al reported that the PPARG expression is related to cancer stages and clinical evolution 39 . G protein-coupled receptors are widely expressed in cells and their downstream signaling pathways are involved in a number of pathological processes [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Our study identi ed the potential vital molecules and signaling pathways related to the LDHA-mediated PDAC.…”
Section: Discussionmentioning
confidence: 99%